Data-driven Strategic Planning - Frederick Burrack; Dorothy Thompson; Jeffrey Ward (Academic Chairpersons Conference Proceedings, 2020)
Participants will explore strategies for strategic planning that focuses on: (a) selecting, locating, and reporting data; (b) guiding common goals and expectations; (c) defining and implementing an action; (d) setting benchmarks and assessable outcomes; and (e) considering the impact on student learning.
Keywords: Strategic Planning Program Administration Data Driven